The Union Defence Force and the 1914 strike : the dynamics of the shadow of the burgher (Historia, 2021)
In January 1914 a general industrial strike took place in the Union of South Africa, which resulted in unrest in the Witwatersrand area. Subsequently the fledgling Union Defence Force, for the first time since its inception in 1912, was called upon operationally by the government to suppress the strike. Because the Defence Force was still in a transformational and integration phase, the Permanent Force was not yet ready to quash the strike on its own, and therefore the commandos of the Citizen Force Reserve were commandeered for service. The traditional commando system of the former Boer republics and of the Transvaal Colony and Orange River Colony were thus briefly revived to quell the 1914 strike, albeit in a new and multifaceted South African milieu. This article focuses on conflict and society and emphasises important social military historiographical aspects in South Africa that have been neglected in the past. It illuminates the zeitgeist and character of Afrikaner society of the day by focusing specifically on the social dynamics and the experience of the "burghers" on commando that participated in the crushing of the strike. Theoretical concepts such as ideological differences, nationalism, leadership, commando and Afrikaner identity, masculinity, nostalgia and white poverty elucidate these experiences and perceptions.  In Januarie 1914 het 'n algehele industriële staking in die Unie van Suid-Afrika uitgebreek wat tot onrus in die Witwatersrand area gelei het. Gevolglik is die Unieverdedigingsmag (UVM) vir die eerste keer sedert sy ontstaan in 1912, operasioneel deur die regering aangewend om die staking te onderdruk. Die UVM was egter midde in 'n organisasie- en integrasieproses en gevolglik was die Staande Mag nog nie gereed om die staking op sy eie te onderdruk nie. Die UVM moes dus noodgedwonge die kommando's van die Burgermagreserwes vir diens opkommandeer. Die tradisionele kommandostelsel van die voormalige Boererepublieke asook die Transvaal- en Oranjerivier-kolonies sou dus vlugtig met die 1914-staking herleef maar in 'n nuwe en veelsydige Suid-Afrikaanse milieu. Die artikel fokus op konflik en gemeenskap en beklemtoon belangrike sosiale militêre historiografiese aspekte in Suid-Afrika wat in die verlede verwaarloos is. Dié artikel belig die tydsgees en karakter van die Afrikaner gemeenskap van destyds, deur te konsentreer op die sosiale dinamika en ondervinding van die burgers wat aan die onderdrukking van die staking deelgeneem het. Onderwerpe, soos ideologiese verskille, nasionalisme, leierskap, kommando en Afrikaneridentiteit, manlikheid, nostalgie en wit armoede werp lig op hierdie ervaringe en omstandighede.
Keywords: 1914-Rebellie; Masculinity; Nostalgia; Nationalism; Militere geskiedenis; Unieverdedigingsmagte